Open Innovation in Medical and Pharmaceutical Research: A Literature Landscape Analysis - Andy Wai Kan Yeung; Andy Wai Kan Yeung; Atanas G. Atanasov; Atanas G. Atanasov; Atanas G. Atanasov; Atanas G. Atanasov; Helen Sheridan; Elisabeth Klager; Fabian Eibensteiner; Fabian Eibensteiner; Sabine Völkl-Kernsock; Maria Kletecka-Pulker; et al. (Frontiers Media S.A., 2021)
Open innovation in medical and pharmaceutical research has grown steadily over the last decade. However, the performance of the published literature in terms of the scientific impact and gaining social media attention remains largely unexplored. The scientific literature of open innovation was examined by means of bibliometric analyses to identify the most prolific authors, organizations, countries, journals, research areas, and recurring terms. By accessing the Web of Science Core Collection and Altmetric electronic databases, citation-related and Altmetric data were evaluated. Public-private partnerships and a selection of newly introduced potential novel drugs in the analyzed publications were identified. North America and Europe were the major literature contributors. Research outputs were mainly published in journals focused on business and economics, pharmacology and pharmacy, and engineering. Many pharmaceutical and biotechnological companies contributed to the analyzed publications, with higher mean citation counts and social media attention (Altmetric score) than nonindustry articles. Public-private partnerships fostered financial support, sharing of expertise and intellectual property, and research collaborations. In summary, open innovation might serve as a powerful strategy to both benefit the involved industry entities and accelerate the development of solutions and products for the betterment of human health.